THE INTENTION TO USE E-COMMERCE TO PURCHASE GREEN COSMETICS WITH A MODIFIED UTAUT2 APPROACH - Kartikasari, Yuliana; Sunaryo, Sunaryo; Yuniarinto, Agung (Universitas Brawijaya, Indonesia, 2021)
The quantitative research examines factors affecting the intention to use e-commerce by employing a modified UTAUT2 model. The sample is 263 e-commerce users in Surabaya, Malang, and Kediri who have e-commerce account and know about Sensatia Botanicals. The Data was analyzed using PLS (Partial Least Square) in SmartPLS 3.0. The results of the analysis indicate that performance expectancy, facilitating conditions, social influence, habit, perceived playfulness and price value have a significant positive influence on the behavior intention to use e-commerce, and that effort expectancy and hedonic motivation do not have any significant positive influence. Gender difference in this study can increase the intention of individuals to use e-commerce on the price value factors, while age and income difference in this study neither increase nor decrease the intention of individuals to use e-commerce to purchase the products of Sensatia Botanicals.